2014
DOI: 10.1161/circulationaha.113.004940
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of β3-Adrenoceptors in Cardiac Myocytes Attenuates Neurohormone-Induced Hypertrophic Remodeling Through Nitric Oxide Synthase

Abstract: 451H emodynamic overload and ischemic or oxidative stress promote adverse cardiac remodeling, a leading cause of worsening heart failure.1,2 Most of these pathophysiologic conditions are associated with (and to a certain extent, mediated by) adrenergic stimulation and catecholamines release, resulting in adrenoceptor (AR) activation on different cell types within the myocardium. Among these, cardiac myocyte β1-ARs are classically considered to mediate short-term positive effects on all aspects of myocardial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
142
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 134 publications
(160 citation statements)
references
References 51 publications
18
142
0
Order By: Relevance
“…The endogenous activation of ␤ 3 ARs was associated with reduced myocardial injury during MI; however, no analysis of fibrosis was provided in this study (8). Moreover, coupling of ␤ 3 ARs to eNOS provided protection from isoproterenol-induced hypertrophy and fibrosis (4). Finally, studies from our own laboratory have revealed that exercise-mediated protective effects on telomere regulation and protection from doxorubicin-induced cardiac damage were mediated by eNOS (82), and eNOS deletion aggravated fibrosis and maladaptive remodeling after pressure overload (30).…”
Section: Adenosine Receptors Are Upregulated By Exercise: a Potentialmentioning
confidence: 74%
“…The endogenous activation of ␤ 3 ARs was associated with reduced myocardial injury during MI; however, no analysis of fibrosis was provided in this study (8). Moreover, coupling of ␤ 3 ARs to eNOS provided protection from isoproterenol-induced hypertrophy and fibrosis (4). Finally, studies from our own laboratory have revealed that exercise-mediated protective effects on telomere regulation and protection from doxorubicin-induced cardiac damage were mediated by eNOS (82), and eNOS deletion aggravated fibrosis and maladaptive remodeling after pressure overload (30).…”
Section: Adenosine Receptors Are Upregulated By Exercise: a Potentialmentioning
confidence: 74%
“…of ␤3-adrenoceptors was reported to inhibit hypertrophic response to ISO in vitro and in vivo through endothelial nitricoxide synthase stimulation (28). Third generation ␤-adrenoreceptor blockers such as Nebivolol have further properties including stimulation of NOS and/or ␤3-adrenoceptors (29).…”
Section: Discussionmentioning
confidence: 99%
“…NPRC, on the other hand, lacks the intracellular guanylate cyclase domain and has been shown to signal to inhibitory guanine nucleotide‐binding protein (inhibitory G protein) 9. Soluble guanylyl cyclase, on the other hand, is activated by nitric oxide and was recently shown to mediate the protective effects of β3‐adrenergic receptor activation on left ventricle (LV) remodeling 10, 11. NP activation, secretion, and signaling in different cell types are summarized in Figure 1.…”
Section: Natriuretic Peptides and Their Receptorsmentioning
confidence: 99%